PENGARUH KEGIATAN PRAMUKA TERHADAP PEMBENTUKAN KARAKTER TANGGUNG JAWAB SISWA DI SMKN 1 BENGKALIS KECAMATAN BENGKALIS KABUPATEN BENGKALIS - Mirfayanti, Mirfayanti; Gimin, Gimin; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: the aim of this study to know is there an influence of scout activitiestowards the formation of character of student responsibility in public vocationalsecondary schools 1 Bengkalis in Bengkalis sub-Bengkalis Distric. As for thepopulation and sample this research is all students in public vocational secondaryschools 1 Bengkalis in Bengkalis sub-Bengkalis Distric who participated in scoutactivities as many as 54 students. By using a saturated sampling technique. Datacollection techniques used are through observation, questionnaires and documentation.In analyzing using simple linear regression analysts. The results of this study indicatethat there is the influence of scout activities on the formation of the character ofresponsibility in public vocational secondary schools 1 Bengkalis in Bengkalis sub-Bengkalis Distric. This is evidenced by a series of simple linear regression tests beteenX and Y variables, obtained F count 54,024 and F table values 4.03 obtained from thestudy of the distribution list F count ith N=54, at a significant level of 5% thus F count> F table or 54.024 > 4.03 then Ho di rejected and Ha received significant meaning,there is the influence of scout activities on the formation of the character ofresponsibility in public vocational secondary schools 1 Bengkalis in Bengkalis sub-Bengkalis Distric.it is expected that with this researc the coach and students canmaintain and also increase scout activites again with innovations and new ideas thatcan support scout activities better and more interesting by being supported by thefacilities and infastructure provided by the schoo.Key Words : Scout, character of student responsibility